2012
DOI: 10.1186/1756-0500-5-131
|View full text |Cite
|
Sign up to set email alerts
|

Conserved phosphoryl transfer mechanisms within kinase families and the role of the C8 proton of ATP in the activation of phosphoryl transfer

Abstract: BackgroundThe kinome is made up of a large number of functionally diverse enzymes, with the classification indicating very little about the extent of the conserved kinetic mechanisms associated with phosphoryl transfer. It has been demonstrated that C8-H of ATP plays a critical role in the activity of a range of kinase and synthetase enzymes.ResultsA number of conserved mechanisms within the prescribed kinase fold families have been identified directly utilizing the C8-H of ATP in the initiation of phosphoryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…It has been demonstrated that the adenyl group of ATP plays a direct role in the control of ATP binding and/or phosphoryl transfer within a range of kinase and synthetase enzymes [1,2]. The role of the ATP C8-H in the binding and/or phosphoryl transfer activity of a number of kinase and synthetase enzymes was elucidated in comparative enzyme activity assays using ATP and ATP deuterated at the C8 position.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the adenyl group of ATP plays a direct role in the control of ATP binding and/or phosphoryl transfer within a range of kinase and synthetase enzymes [1,2]. The role of the ATP C8-H in the binding and/or phosphoryl transfer activity of a number of kinase and synthetase enzymes was elucidated in comparative enzyme activity assays using ATP and ATP deuterated at the C8 position.…”
Section: Introductionmentioning
confidence: 99%
“…The functionality required for the catalysis and regulation of phosphoryl transfer was found to be conserved within the families or fold-groups. As a result, a number of conserved mechanisms were proposed, wherein the C8-H of the adenyl moiety was found to play a direct role in the control of phosphoryl transfer [2]. These mechanisms were developed using structurally conserved amino acid residues within hydrogen-bonding distance of a nucleotide in the active sites of crystallised kinases of a particular mechanistic class.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The known ATP binding sites in kinases also define the approximate substrate positions in the vicinity of the γ-phosphates of ATP26. In Apcα, the potential substrate binding site resembles similarly-sized pockets in pantothenate or acetate kinases2327 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…34,35 These enzymes normally hold two Mg 2+ ions placed into the active site which assist the phosphorylation catalysis (the role of Mg 2+ ions will be discussed in the section 4.2).…”
Section: Enzymatic Catalysismentioning
confidence: 99%